Measurement of Nitrate Reductase Activity in Vivo Using Sepctrophotometry Method - Mose, Windi; Dorlandt, Mauritius; Wael, Syahran; Riupassa, Pieter Agusthinus (RUMPHIUS, 2025)
Spectrophotometry is a quantitative measurement technique of a compound based on the measurement of absorbance or light transmission passing through the compound. The spectrophotometric method can be used to analyze the content of compounds. One of the enzymes whose activity can be measured in vivo is the nitrate reductase enzyme. The nitrate reductase enzyme is an enzyme that plays a role in the synthesis of ammonium and amino acids. The results of measuring the activity of the nitrite reductase enzyme with spectrophotometry showed that the highest NRA value was found in the leaves of red chili plants and the lowest was in the sugarcane leaf sample. NRA can be used as a selection parameter to predict the results of a plant, and has the potential to be applied to seed plants.